2018
DOI: 10.1590/0037-8682-0050-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal meningitis epidemiology: 17 years of experience in a State of the Brazilian Pantanal

Abstract: The present study documents the occurrence of neurocryptococcosis, which is mainly caused by C. neoformans VNI, in Mato Grosso do Sul, Brazil, with probable autochthonous cases in the Brazilian Pantanal, the world's largest tropical wetland, and a biome where cryptococcosis has not yet been explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…This extends the B cell characterization in these HIV-coinfected subjects. However, we could not determine whether the prominent B cell subset and activation perturbations in blood were due to the chronic effects of advanced HIV disease alone or due to an additional effect of acute secondary infection where cryptococcal antigen and symptoms develop 1 to 4 weeks prior to diagnosis (19,20,28,29). This distinction is important in determining whether patients with such advanced disease can actually generate a specific response to this systemic and local neurologic cryptococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…This extends the B cell characterization in these HIV-coinfected subjects. However, we could not determine whether the prominent B cell subset and activation perturbations in blood were due to the chronic effects of advanced HIV disease alone or due to an additional effect of acute secondary infection where cryptococcal antigen and symptoms develop 1 to 4 weeks prior to diagnosis (19,20,28,29). This distinction is important in determining whether patients with such advanced disease can actually generate a specific response to this systemic and local neurologic cryptococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in China with 954 cases of HIV infection found that (7.3%) had association with cryptococcal infection (PANG et al, 2018). In Brazil, a study showed that most isolates of C. neoformans (87.5%) were obtained from patients with HIV (NUNES et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, mortality rate ranged from 32% to 60% in HIV-infected population. Meningeal cryptococcosis mostly caused by C. neoformans occurs predominantly in these patients despite highly active antiretroviral therapy being widely distributed in Brazil [58], [59], [60].…”
Section: Systemic Mycosismentioning
confidence: 99%
“…and Epidermophyton floccosum Cosmopolitan diseasePeople with dry skin, school-age children, rural workers and athletes. People with diabetes, HIV/AIDS infection, immunosuppressed and obeseSubcutaneousSporotrichosis [29], [31] Sporothrix spp.Higher incidence occurs in Rio de Janeiro and São PauloChildren or housewives with frequent contact with domestic and stray catsChromoblastomycosis [23], [25], [26], [27] Fonsecaea, Cladophialophora and Rhinocladiella Higher incidence occurs in Maranhão and ParáRural workers, mainly babassu extractorsSystemic (primary pathogens)Paracoccidioidomycosis [37], [38], [39], [41], [42], [44] Paracoccidioides spp.Several endemic areas with higher incidence: São Paulo, Paraná, Rio Grande do Sul, Goiás; and also regions with progressive devastation of tropical forestsWorking-age men and farmers in contact with soilHistoplasmosis [47], [48] Histoplasma capsulatum Higher incidence occurs in regions with caves and/or with progressive devastation of tropical forestsHIV/AIDS patients, rural workers, speleologists, tourists in contact with bat guano and soilCoccidioidomycosis [49], [50], [52], [53] Coccidioides immitis Endemic areas with dry climates, mainly Piauí, Ceará, Bahia and Maranhão; also regions with progressive devastation of tropical forestsRural workers, armadillo hunters and constructors in contact with soilOpportunistic yeasts and mouldsCandidiasis [12], [13], [69], [70], [71] (dermatitis, mucocutaneous, bloodstream) Candida spp.Cosmopolitan diseaseImmunocompromised hosts, HIV/AIDS patients, patients with haematologic cancer and stem-cell transplant recipientsCryptococcosis [57], [58], [59] Cryptococcus spp.Cosmopolitan diseaseImmunocompromised male hosts, HIV/AIDS patients, transplant recipientsAspergillosis and fusariosis [72], [73], [74], [75] Aspergillus spp., Fusarium spp.Cosmopolitan diseaseHospitalized and immunocompromised hosts, patients with HIV/AIDS, haematologic cancer and st...…”
Section: Introductionmentioning
confidence: 99%